Gold nanoparticles as scaffolds for poor water soluble and difficult to vehiculate antiparkinson codrugs. (6th December 2016) - Crescenzo, A Di; Cacciatore, I; Petrini, M; D'Alessandro, M; Petragnani, N; Boccio, P Del; Profio, P Di; Boncompagni, S; Spoto, G; Turkez, H; Ballerini, P; Stefano, A Di; et al.
Abstract: We report the facile and non-covalent preparation of gold nanoparticles (AuNPs) stabilized by an antiparkinson codrug based on lipoic acid (LA). The obtained AuNPs appear stable in both dimethyl sulfoxide and fetal bovine serum and able to load an amount of codrug double the weight of gold. These NPs were demonstrated to be safe and biocompatible towards primary human blood cells and human neuroblastoma cells, one of the most widely used cellular models to study dopaminergic neural cells, therefore are ideal drug carriers for difficult to solubilize molecules. Very interestingly, the codrug-stabilized AuNPs were shown to reduce the accumulation of reactive oxygen species in SH-SY5Y cells treated with LD and did not change total oxidant status levels in cultured human blood cells, thus confirming the antioxidant role of LA although bound to AuNPs. The characterization of AuNPs in terms of loading and stability paves the way for their use in biomedical and pharmacological applications.